Influence of Self-Actualization Needs and Professional Development on the Job Performance among Technology and Livelihood Education (TLE) Teachers - Angelo Obediente (Journal of General Education and Humanities, 2023)
This study attempted to determine the relationship between Self-Actualization Needs and Professional Development on Job Performance among Technology and Livelihood Education Teachers. A descriptive correlational method and survey questionnaire were utilized to attain the study's objectives among the 54 TLE teachers in Sto. Tomas South District, the majority are female whose age ranges from 26-30 years old, serving for four years and above in the Department of Education, with master’s unit and with above ten numbers of training attended. The results showed the level of their self-actualization needs and much weight on active participation in school meetings conducted by the school head. The respondents’ professional development level focused on skills in preparing an appropriate learning environment. Therefore, using Mother Tongue, Filipino, and English is essential to teaching and learning. It was concluded that the input variables were significantly related to self-actualization needs; likewise, the professional development of teachers was found to be significantly related to all measures of job performance. The following recommendations are at this moment offered; educators could engage in assessments that will develop their characteristics in life satisfaction and personal growth, providing instruction on implementing teaching materials and activities.